2019
DOI: 10.1016/j.gaitpost.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability and minimal detectable change of ankle kinematics and spatiotemporal parameters in MS population

Abstract: Background Many people with multiple sclerosis (pwMS) experience walking impairments often including foot drop, evident as either reduced dorsiflexion at initial contact and/or at the swing phase of the gait cycle. To measure even subtle differences in ankle kinematics 3D gait analysis is considered a 'gold' standard. However, the psychometric properties of ankle kinematics in the MS population have not yet been examined. Objective The aim of the study was to examine test-retest relative and absolute reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Minimal detectable change (MDC) values for these spatiotemporal gait parameters have been measured for a variety of pathological populations, including chronic stroke patients (Geiger et al, 2019), adults with multiple sclerosis (Andreopoulou et al, 2019), post-incomplete spinal chord injury patients (Nair et al, 2012), chronic low back pain patients (Fernandes et al, 2015), and adults with cerebral palsy (Levin et al, 2019), and range from 0.11 m/s to 0.23 m/s for gait speed, 4 cm to 17 cm for step length, 8 cm to 17 cm for stride length, and 2 cm to 3 cm for stride width. Similarly, time-based gait parameter MDC values have been reported as 0.04 s to 0.05 s for step time, 0.09 s for cycle time, 0.03 s to 0.28 s for swing time, 0.06 s to 0.09 s for stance time, and 0.03 s to 0.69 s for double limb support time (Fernandes et al, 2015;Nair et al, 2012;Wittwer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Minimal detectable change (MDC) values for these spatiotemporal gait parameters have been measured for a variety of pathological populations, including chronic stroke patients (Geiger et al, 2019), adults with multiple sclerosis (Andreopoulou et al, 2019), post-incomplete spinal chord injury patients (Nair et al, 2012), chronic low back pain patients (Fernandes et al, 2015), and adults with cerebral palsy (Levin et al, 2019), and range from 0.11 m/s to 0.23 m/s for gait speed, 4 cm to 17 cm for step length, 8 cm to 17 cm for stride length, and 2 cm to 3 cm for stride width. Similarly, time-based gait parameter MDC values have been reported as 0.04 s to 0.05 s for step time, 0.09 s for cycle time, 0.03 s to 0.28 s for swing time, 0.06 s to 0.09 s for stance time, and 0.03 s to 0.69 s for double limb support time (Fernandes et al, 2015;Nair et al, 2012;Wittwer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GSTP in pwMS, absolute and relative reliability of GSTP have been studied [ 71 ] in populations with lower (0–3.5) and higher (4–6) EDSS scores, and this study showed that higher walking disability in pwMS was associated with higher within-subject variability. These results are consistent with our review findings showing that clinical researchers less often chose this kind of assessment in pwMS with lower gait capacities.…”
Section: Discussionmentioning
confidence: 88%
“…Despite this fact, studies on the psychometric properties of these methods is needed. This point was already pointed out by Andreopoulou in 2019 [ 71 ], stating that although 3D gait analysis is considered a “gold” standard, psychometric properties of some of the measures provided by these technological systems have not been examined in pwMS. They studied the relative and absolute reliability of ankle kinematics and GSTP provided by VICON system in a sample of 49 pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal detectable change (MDC) was calculated using the relation: SEM × 1.96 × √ 2 [29]. The MDC indicates the minimum amount of change that is not likely to be due to an accidental error in measurement [30]. Pearson and Spearman correlation coefficients were used to examine the relationships between variables.…”
Section: Discussionmentioning
confidence: 99%